Using Digital Portfolios to Develop Students’ Writing: A Practical Guide for Language Teachers. Lam, R., & Moorhouse, B., L. (2022) Abingdon, Routledge, 167 pages, ISBN: 978-1-032-28240-4 - Estaji, Masoomeh; Ghiasvand, Farhad (Porta Linguarum Revista Interuniversitaria de Didáctica de las Lenguas Extranjeras, 2024)
The uses of e-portfolios in L2 education and research have recently increased given their reflective and process-oriented nature. Many scholars have begun using e-portfolios to collect their data in various aspects of L2 teaching and learning. Considering the prominence of technologies and e-portfolios in teaching L2 writing, a recent and influential book has been published by Routledge titled “Using Digital Portfolios to Develop Students’ Writing: A Practical Guide for Language Teachers”. It presents the theoretical underpinnings of e-portfolio and the way its application in L2 contexts can boost the quality of teaching and learning English writing skills.